Investment and financing considerations: Evidence from Finnish panel data - Anne Brunila (Bank of Finland, 1994)
This paper presents a simple intertemporal model for the determination of corporate investment when the required rate on debt financing depends on the financial risk involved. When the actual lending rate does not fully reflect the financial risk, the balance sheet position of firms affects investment, as do the lending rate and demand factors. Specifically, the model implies that investment decreases with the amount of debt financing and increases with the availability of new equity financing and cash flow. Moreover, the financing conditions should be more important the greater the leverage. Empirical results using Finnish panel data over the period 1985-92 conforms with the predictions of the theoretical model.
URN:NBN:fi:bof-201808031877
Keywords: 330